Polyimide for Electronic and Electrical Engineering Applications - Diaham, Sombel (IntechOpen, 2021)
Polyimide is one of the most efficient polymers in many industries for its excellent thermal, electrical, mechanical, and chemical properties as well as its easy processability. In the electronic and electrical engineering industries, polyimide has widely been used for decades thanks to its very good dielectric and insulating properties at the high electric field and at high temperatures of around 200°C in long term-service. Moreover, polyimide appears essential for the development of new electronic devices where further considerations such as high power density, integration, higher temperature, thermal conduction management, energy storage, reliability, or flexibility are required in order to sustain the growing global electrical energy consumption. This book gathers interdisciplinary chapters on polyimide in various topics through state-of-the-art and original ongoing research.